Assessment of Mycoplasma gallisepticum vaccine efficacy in a co-infection challenge model with QX-like infectious bronchitis virus. Issue 3 (4th May 2018) - Bwala, Dauda G.; Solomon, Ponman; Duncan, Neil; Wandrag, Daniel B.R.; Abolnik, Celia
ABSTRACT: Mycoplasma gallisepticum (MG) is the primary cause of chronic respiratory disease in poultry. We investigated the protective efficacy of the live-attenuated ts-11 and 6/85 MG vaccines against a local MG strain and, in order to enhance signs and mimic a typical field situation, we co-infected birds with a virulent strain of QX-like infectious bronchitis virus (IBV). Both vaccines showed similar ability to protect infected chickens from clinical signs, although ts-11 performed slightly better. Despite the lower protection against clinical disease, 6/85-vaccinated birds had significantly ( P  ≤ 0.05) lower tracheal lesion scores and mucosal thickness at day 28 post-vaccination (7 days post-challenge [dpc] with MG, 2 dpc IBV) and day 31 post-vaccination (10 dpc MG challenge, 5 dpc IBV) compared to ts-11 vaccinated birds, but these difference was not significant at day 33 (12 dpc MG, 7 dpc IBV). Pathogen infection and replication was assessed by qPCR, and the 6/85 vaccine produced a more significant ( P  ≤ 0.05) reduction in MG replication in the lungs, kidneys and livers but enhanced late replication in bursae and caecal tonsils. In contrast, the ts-11 vaccine had a more pronounced reductive effect on replication in tracheas, air sacs, bursae and heart at days 28 and 31, yet increased replication in lungs. Interestingly, both vaccines provided non-specific protection against IBV challenge. The co-challenge model provided useful data on vaccine efficacy, especially on days 31 and 33, and tracheas, lungs, air sacs, kidneys, liver and caecal tonsils were the best organs to assess.